Odpowiedzi

2009-11-13T22:22:19+01:00
3x+ 3y- 2z = 3
2 x - 5y = -8
x + 4z = 13

2z=3-3x-3y
2x-5y=-8
x+3-3x-3y=13

2z=3-3x-3y
2x-5y=-8
-2x-3y=10

2z=3-3x-3y
2x=-8+5y
8+5y-3y=10

2z=3-3x-3y
2x=-8+5y
2y=2
y=1

2z=3-3x-3y
2x=-8+5y
y=1

2z=3-3x-3y
2x=-8+5
y=1


2z=3-3x-3y
x=-1,5
y=1

2z=3-4,5-3
x=-1,5
y=1
z=5,25









2009-11-13T22:24:06+01:00
3x+ 3y- 2z = 3
2 x - 5y = -8
x + 4z = 13



Wyznaczamy wyznacznik macierzy współczyników

W=/3 3 -2/
/2 -5 0/= 10+24=60=94
/1 0 4/
W(X)= /3 3 -2/
/-8 -5 0/=130-96+60=94
/13 0 4/
W(Y)=/3 3 -2/
/2 -8 0/=-96-52-16-24=-188
/1 13 4/

W(Z)=/3 3 3/
/2 -5 -8/=-15+78+195+24=282
/1 0 13/
x=W(X)/W= 94/94=1
y=W(Y)/W=-188/94=-2
z=W(Z)/W=282/94=3